2014
DOI: 10.1016/j.amjcard.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flow and Left Ventricular Strain on Outcome of Patients With Preserved Left Ventricular Ejection Fraction and Low Gradient Severe Aortic Stenosis Undergoing Aortic Valve Replacement

Abstract: The prognostic implications of flow, assessed by stroke volume index (SVi), and left ventricular (LV) global longitudinal strain on survival of patients with low gradient severe aortic stenosis (AS) and preserved left ventricular ejection fraction (LVEF) are debated. The aim of this study was to evaluate the impact of flow and LV global longitudinal strain on survival of these patients treated with aortic valve replacement (AVR). Low gradient severe AS patients with preserved LVEF treated with AVR (N=134, age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…Nonetheless, there are studies that demonstrated the improvement of all three components of the strain in short-term follow-up on a small sample size or using intraprocedural transesophageal echocardiography, but only changes in GLS persisted during follow-up [42,43]. The analysis of our cohort data demonstrated that GLS correlates with the complication rate, concordant with other studies where GLS distinguished itself as a prognostic parameter for major adverse cardiac events and was superior to LVEF [18,22,44]. Mitral regurgitation, paravalvular leaks or permanent pacemaker implantation are also factors that influence on left ventricular recovery, but we could not observe any significant correlation in our cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, there are studies that demonstrated the improvement of all three components of the strain in short-term follow-up on a small sample size or using intraprocedural transesophageal echocardiography, but only changes in GLS persisted during follow-up [42,43]. The analysis of our cohort data demonstrated that GLS correlates with the complication rate, concordant with other studies where GLS distinguished itself as a prognostic parameter for major adverse cardiac events and was superior to LVEF [18,22,44]. Mitral regurgitation, paravalvular leaks or permanent pacemaker implantation are also factors that influence on left ventricular recovery, but we could not observe any significant correlation in our cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Even in the multivariate analysis, this difference in the GLSR was maintained. Recently, it has been reported that a deterioration of GLS in PLGAS would be a predictor of poor prognosis, suggesting a bene t in asymptomatic patients with early aortic valve replacement [23]. We have demonstrated this signi cant decrease in the longitudinal deformity despite the absence of difference in LVEF between the two groups.…”
Section: Discussionsupporting
confidence: 57%
“…Serial measurement of SVI and Z VA , as well as assessment of LV strain,14 35 36 may be helpful in guiding therapy. Several studies including relatively small numbers of patients with LF/LG AS and preserved EF have assessed the impact of surgical (AVR) and transcatheter AVR on survival (table 1)7 9 31 33–43; most demonstrated a benefit with AVR.…”
Section: Managementmentioning
confidence: 99%